"Absolute safety of the irrigation pivots in El-Oued region - Algeria " - محمد أمين, قروي; فارس, حني; حمزة, بهى (University of El-Oued, 2021)
"The region of El Oued in the south-east of Algeria is a very important agricultural area. Farmers in this region have a very dangerous problem with the irrigation pivots. The latter took several lives of agriculture by electrification. The aim of our work is to offer a very safe and inexpensive solution that can save the life of agriculture and its breeding. We proposed to install the panels horizontally on the pivot so that the solar rays cover the entire surface of the panel. Then we did another experiment, pushing the panels at a slight angle to prevent water precipitation on the surface of the panels and to prevent the formation of a layer of limestone on the panels. By comparing the two experiments, we obtained that the yields of the two experiments are very similar, which is why we favored the use of panels with a slight angle as a solution to our problem. Key words: irrigation pivot, solar energy, Farmers, solar panel, solar rays. " تعتبر منطقة الواد جنوب شرق الجزائر منطقة زراعية مهمة للغاية. يعاني المزارعون في هذه المنطقة من مشكلة خطيرة للغاية مع محاور الري. هذا الأخير أودى بحياة العديد من المزارعين بالتكهرب. الهدف من عملنا هو تقديم حل آمن للغاية وغير مكلف يمكن أن ينقذ حياة المزارعين ومواشيهم. اقترحنا هو تثبيت الألواح الشمسية أفقيًا على المحور بحيث تغطي الأشعة الشمسية كامل سطح اللوحة. ثم قمنا بتجربة أخرى حيث وضعنا الألواح بزاوية صغيرة لمنع احتقان المياه على سطح الألواح ولمنع تكون طبقة من الحجر الجيري على الألواح. بمقارنة التجربتين، توصلنا إلى أن نتائج التجربتين متقاربة جدً، ولهذا فضلنا استخدام الألواح بزاوية طفيفة كحل لمشكلتنا.
Electromécanique مذكرة ماستر تخصص
Keywords: irrigation pivot, solar energy, Farmers, solar panel, solar rays.; محور الري، الطاقة الشمسية، المزارعون، الألواح الشمسية، الأشعة الشمسية.